Efforts to Increase Students' Interest in Choosing Islamic Boarding School Students Through Strengthening Person Contact Based Public Relations Management - Rohmawati, Zulfa; Abun, A. Rifa’i; Hidayah, Nur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the management of public relations (PR) as a liaison in increasing prospective students' interest in choosing Islamic boarding schools at Pondok Pesantren Al Mujtama' Al Islami, Al Ishlah, and Al Huda. The research employed a qualitative approach with a multisite research design conducted at the three Islamic boarding schools through direct observation, in-depth interviews, and documentation analysis. Informants included kiai, Islamic boarding school leaders, public relations managers, teachers, parents, and alumni, while data collection techniques consisted of observation, semi-structured interviews, and document review. Data analysis followed Miles and Huberman's interactive model involving data reduction, data display, and conclusion drawing.The findings show that public relations management in the three Islamic boarding schools is implemented through diverse approaches, ranging from structured and program-based communication strategies to traditional interpersonal practices rooted in religious values ​​and community trust. The public relations function serves as a strategic communication bridge between Islamic boarding schools and society through socialization activities, alumni networks, community engagement, and limited use of digital media. These practices contribute to the formation of institutional image and the strengthening of public trust, which subsequently influences prospective students' interests. Challenges identified include limited professional human resources, low levels of digital literacy, and constraints in optimizing modern communication media.